Lessons learned from the case study of a university-based teacher education program for second career adults: stakeholder views over 18 years - Butler, Alexandra S., author; Lehmann, Jean P., advisor; Uchiyama, Kay, advisor (Colorado State University. Libraries, 2007)
In recent years the need for teachers has brought discussions about alternative teacher training models to the forefront (Huling, 2001; Levine, 2006). This study was conducted to understand best practices related to one type of alternative teacher education program; a fast track university graduate education program for second-career adults. The researcher used an embedded case study methodology with four stakeholder groups; program graduates (n=101 or 50% of the available sample), program directors (n=6), university administrators (n=6), and selected employers of graduates (n=6). The graduates completed an online survey addressing their satisfaction in the program. The researcher conducted hour-long interviews with the other three participant groups to further explore factors that either positively or negatively affected the program's implementation. Additionally the researcher reviewed program archival materials.

Findings were that the majority of the program graduates responding were satisfied with the program (mean = 4.53) and would recommend it to others (mean 4.55). The respondents reported that the use of a cohort model that interspersed learning with classroom experience, extensive and varied classroom pedagogies, and the use of research -based curriculum as having provided them with a sound foundation for entering the teaching profession. Frequent feedback and mentoring in the field were also perceived as being important factors for the program's success. Graduate survey responses were confirmed by the interviews with the three other stakeholder groups. University administrators identified barriers to program implementation and sustainability to include its high delivery cost, the lack of communication with the traditional licensure program, limited documentation of program strengths, and the disconnection with university and departmental practices. Further the intensive nature of the program's delivery was perceived as a hardship for involved faculty.

Recommendations were to make completing the masters mandatory, not optional; to seek to meet content area needs identified by school district partners; to have strong administrative support; to create communication mechanisms for maintaining a strong presence in the university and to conduct evaluation and research studies providing data for ongoing reflection and renewal.
Keywords: case study; cohort; collaborative model; fast track; graduate education; graduate level teacher education; second career; second-career adults; stakeholders; teacher education; teacher education